1272Effect of age, genetic background and experimental conditions on left atrial monophasic action potential duration, effective refractory period and activation time in Langendorff-perfused murine hearts. (18th June 2020) - Obergassel, J; Kabir, S N; O"reilly, M; Sommerfeld, L C; O"shea, C; Eckardt, L; Kirchhof, P; Fabritz, L
Abstract: Funding Acknowledgements: Supported by EU [CATCH ME] 633196, British Heart Foundation FS/13/43/30324, AA/18/2/34218 LF, PK, DFG FA413 LF, Studienstiftung to JO. Background: Studying cardiac electrophysiology in isolated perfused beating murine hearts is a well-established method. The range of normal values for left atrial action potential durations (LA-APD), activation times (LA-AT) and effective refractory periods (atrial ERP) in murine wildtype (WT) is not well known. Purpose: This study aimed to establish reference values for LA-APD, LA-AT and atrial ERP and to identify factors that influence these electrophysiological parameters in wildtype (WT) mice. Method: We combined results from isolated beating heart Langendorff experiments carried out in WT between 2005 and 2019 using an octopolar catheter inserted into the right atrium and a monophasic action potential electrode recording from the LA epicardium. Electrophysiological parameters (LA-APD at 50%, 70%, 90% repolarization (APD50, APD70, APD90), LA-AT and atrial ERP) at different pacing cycle lengths (PCL) were summarized. We analyzed effects of PCL, genetic background, age, gender, heart weight to body weight ratio (HW/BW), LA weight to body weight ratio (LAW/BW) as well as coronary flow and temperature as experimental conditions. Results: Electrophysiological parameters from 222 isolated hearts (114 female, mean age 6.6 ± 0.25 months, range 2.47-17.7 months) of different backgrounds (77 C57BL/6, 23 FVB/N, 33 MF1, 69 129/Sv and 20 Swiss agouti) were combined. Coronary flow rate, flow temperature and start of isolation to cannulation time were constant experimental conditions over the timespan of experiments. LA-APD was longer while LA-AT decreased with longer PCL throughout all genetic backgrounds (Figure 1A). Genetic background showed strong effects on all electrophysiological parameters. LA activation was delayed in 129/Sv compared to other backgrounds (Figure 1D). LA-APD70 and atrial ERP were significantly shorter in Swiss agouti background compared to others. LA-APD70 was also significantly prolonged in 129/Sv background compared to MF1 (Figure 1C). Atrial ERP was longer in FVB/N compared to other backgrounds. Age effects were compared in groups. Atrial ERP was significantly longer in mice ≤ 3 months compared to all older mice. Atrial ERP was also significantly prolonged (+ 3.4ms, + 13.5%) in female mice compared to males (Figure 1B). Conclusion: This dataset summarizes left atrial electrophysiological parameters in the beating mouse heart and can serve as a reference for design and interpretation of electrophysiological experiments in murine models of commonly used genetic backgrounds. We confirm that cycle length, genetic background, age and gender affect atrial electrophysiological parameters. Awareness of these will support successful experimental design.